(untitled) (Tabularium Historiae, 2020)
Although Dominicans arrived in Chełmno in the 1230s, the beginnings of their monastery remain unclear. The orders’ temple was being built from the late 13th century to the turn of the 14th century, and rebuilt three hundred years later. Its history of construction is written in detail due to architectural investigations (2010–2015). That research did not contain the friary because it was demolished soon after its burning in 1830. Lack of archaeological surveys and tentative plans of the city from the 18th and 19th century made most scholars overlook the spatial complexity of the monastery, even in the most recent publications. This paper aims to fulfil the lack of knowledge about the final spatial form of the Dominican Monastery (from the beginning of the 19th century) and to analyze the plans and investments of Protestants who took the former friary’s land after its dissolution. The author conducted interdisciplinary research joining the results of the archival query and the architectural investigation of the northern church wall. This consideration allows him to reconstruct the final form of the monastery and describe the actions conducted after its demolition. At the beginning of the 19th century, brothers lived in the new baroque western wing. There existed a rectangular cloister and the appendix with a kitchen. Before the western façade of the church, there was located the chapel of St. Hyacinth and Baroque narthex, which covered the lower parts of the Gothic church. The medieval sacristy had to be out of use before the demolition of the whole complex in the 1830s. On the example of the Dominican complex in Chełmno, it might be observed the different politics concerning the medieval architecture in Prussia in the 19th century from neglecting its value to acceptation and attempts of protection. This paper is to build a basis for further research (particularly archaeological surveys) on the area of the former monastery.